If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -3 = 5x + 10 Reorder the terms: -3 + 10x = 5x + 10 Reorder the terms: -3 + 10x = 10 + 5x Solving -3 + 10x = 10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -3 + 10x + -5x = 10 + 5x + -5x Combine like terms: 10x + -5x = 5x -3 + 5x = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 -3 + 5x = 10 + 0 -3 + 5x = 10 Add '3' to each side of the equation. -3 + 3 + 5x = 10 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 10 + 3 5x = 10 + 3 Combine like terms: 10 + 3 = 13 5x = 13 Divide each side by '5'. x = 2.6 Simplifying x = 2.6
| -14x+5y=19 | | 4(b-6)=71-2b | | 15+18-12=x | | 10p(1+9p)=8p^2 | | .667x+5=4 | | 8+20(3x+1)= | | 12x-8=8x-28 | | 2x-27-10=16 | | 4+x+3= | | x*5x=20 | | 2m+5=5m-7-5m | | -10x+2=10 | | 4x^2+10x=x+8 | | -10(-v+3)+6(v-11)=v+3+6 | | 54=4x^2-2X-2 | | (6x+2)=(5x+7) | | b*5a=20 | | 3(x+1)=5x-6 | | 4x+7=2-(8x-8) | | 2x+4y+6y-3xy=0 | | 5t+(2t-1)+t=27 | | 26+12-18=x | | 3x(x^2+9)=0 | | pie=7x+2y | | -6w+2=-28 | | -8(a-10)=-8(a-1)+2 | | 12y(y-3)=15y | | (4x+8)-3=92 | | 6a+4b-9a+5ab-8b= | | 12-(.8)(x+15)=4 | | 8-2x=-3 | | -4+3/2x=/2x |